2019
DOI: 10.3390/app9183811
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fabrication Method for Compliant Silicone Phantoms of Arterial Geometry for Use in Particle Image Velocimetry of Haemodynamics

Abstract: Cardiovascular diseases (CVDs) are one of the leading causes of death globally. In-vitro measurement of blood flow in compliant arterial phantoms can provide better insight into haemodynamic states and therapeutic procedures. However, current fabrication techniques are not capable of producing thin-walled compliant phantoms of complex shapes. This study presents a new approach for the fabrication of compliant phantoms suitable for optical measurement. Two 1.5× scaled models of the ascending aorta, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In general, walled flow phantoms present their own unique set of challenges such as increased difficulty in creating complex geometries and consistent wall thickness along with increased cost. 7 , 40 , 59 Additionally, this study utilized continuous flow whereas pulsatile flow is often desired for cardiovascular flow phantoms. Preliminary experimentation has qualitatively shown realistic mechanical reactions of the gel phantoms in response to pulsatile flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, walled flow phantoms present their own unique set of challenges such as increased difficulty in creating complex geometries and consistent wall thickness along with increased cost. 7 , 40 , 59 Additionally, this study utilized continuous flow whereas pulsatile flow is often desired for cardiovascular flow phantoms. Preliminary experimentation has qualitatively shown realistic mechanical reactions of the gel phantoms in response to pulsatile flow.…”
Section: Discussionmentioning
confidence: 99%
“…This may be important in using the phantoms for pulsatile flow applications, since compliance is known to be inversely proportional to wall thickness. 59 Further mechanical testing may be warranted, such as tensile testing and dynamic mechanical analysis to elucidate the elastic and viscous responses, with the extension of methods where tension and oscillatory forces become more prevalent. 8 …”
Section: Discussionmentioning
confidence: 99%
“…A greater wall thickness is advantageous for robustness of these models; however, it can be a limiting factor when trying to accurately simulate vessel behavior that is seen clinically. Studies that have utilized fluid–structure interaction (FSI) have reported that rigid wall assumptions can lead to an overestimation of wall shear stress (WSS) in comparison with a compliant phantom ( 27 , 28 ). In addition, wall stiffness is a measure of arterial health, and the pulse waveform can vary in stiff and compliant arteries.…”
Section: Characteristics Of Current In-vitro Modelsmentioning
confidence: 99%
“…Particle Image Velocimetry is currently one of the best tools to determine the vector velocity field. In the industrial practice, the application possibilities of this technique have been widely documented, for example in mechanical engineering [15], process engineering [16], medicine [17], environmental engineering [18] and power industry [19]. The most important problem nowadays is the choice of appropriate measurement setup and its optical and software configuration [14].…”
Section: Introductionmentioning
confidence: 99%